A Successful Pregnancy in a Hemihysterectomized Patient-A Case Report - Sofia Jovina Domingues; Luísa Pinto (Hindawi Limited, 2022)
Introduction. Didelphys uterus, two separate uterine horns or a double uterus with two separate cervices, is one of several congenital uterine anomalies (CUA), accounting for 5% of CUA. CUA could be associated with dysmenorrhea, pelvic pain, and decreased fertility. During pregnancy, it has been associated with higher risk of miscarriage, preterm birth, malpresentation, and fetal growth restriction. There still is insufficient evidence on the efficacy and safety of surgical interventions in CUA, including hemihysterectomy, in what improvement of reproductive performance is concerned. Objective. The aim of the present case report is to review the literature and complement information on pregnancy outcomes after hemihysterectomy, contributing to a better counseling of women planning a pregnancy under these circumstances. Case Presentation. This paper case reports a successful pregnancy in a woman previously submitted to a hemihysterectomy and removal of a vaginal septum by hysteroscopy, due to a symptomatic didelphys uterus. An ipsilateral renal agenesis was also present. A cesarean was performed at 38 weeks' gestation and a healthy baby was born. Discussion. This paper reports an exceptional clinical situation, with only 9 cases described in the last 6 decades. As in previously reported cases, a cesarean was performed at term, resulting in a live childbirth. In these cases, a higher live birth rate and a lower incidence of preterm deliveries was found, comparing with uterine didelphys pregnancies. Conclusion. Understanding both the exact nature of a uterine anomaly before a surgical treatment and the prognosis for a future pregnancy after the intervention are of paramount importance for precise counseling of future parents.